2008
DOI: 10.3174/ajnr.a1162
|View full text |Cite
|
Sign up to set email alerts
|

Medulla Oblongata Volume: A Biomarker of Spinal Cord Damage and Disability in Multiple Sclerosis: Fig 1.

Abstract: BACKGROUND AND PURPOSE: While brain MR imaging is routinely performed, the MR imaging assessment of spinal cord pathology in multiple sclerosis (MS) is less frequent in clinical practice. The purpose of this study was to determine whether measurements of medulla oblongata volume (MOV) on routine brain MR imaging could serve as a biomarker of spinal cord damage and disability in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
(62 reference statements)
4
30
1
Order By: Relevance
“…ICC at these levels were also high, ranging between 0.94 and 0.99), indicating that nearly all measurement variabilities were due to inter-subject differences rather than measurement errors. These figures are similar to those previously obtained in the medulla oblongata by Liptak et al (intra-rater ICC 0.97) (Liptak et al, 2008). Compared with cord area measures over 0.5 cm segments, measurement reproducibility in 1 mm segments was similar when a single rater undertook the analysis, but noticeably lowers when three raters analyzed the MRI data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ICC at these levels were also high, ranging between 0.94 and 0.99), indicating that nearly all measurement variabilities were due to inter-subject differences rather than measurement errors. These figures are similar to those previously obtained in the medulla oblongata by Liptak et al (intra-rater ICC 0.97) (Liptak et al, 2008). Compared with cord area measures over 0.5 cm segments, measurement reproducibility in 1 mm segments was similar when a single rater undertook the analysis, but noticeably lowers when three raters analyzed the MRI data.…”
Section: Discussionsupporting
confidence: 90%
“…Previous work employing a manual segmentation method has found that medulla oblongata volume is correlated with upper cervical cord volume (Pearson r=0.67) and brain parenchymal fractional volume (r=0.45); however these correlations did not significantly differ i.e. medulla oblongata volume was not significantly more representative of the cervical cord than the brain (Liptak et al, 2008). Cord area measures are also usually assessed over a 1.5 cm segment (Losseff et al, 1996;Kearney et al, 2014b), but the longer the segment used the smaller the chance it will have been included in brain imaging.…”
Section: Introductionmentioning
confidence: 65%
“…The discrepancy to our present findings, with a lack of such correlations in our healthy control group, may be due to a considerably larger study population and a broader age range in the investigations by Engl et al The relative amounts of pathological and physiological components are difficult to judge from our patient data, but DTI studies have independently confirmed, that considerable infratentorial corticospinal tract degeneration exists in RRMS and SPMS compared to healthy controls (Preziosa et al, 2011), Furthermore, in MS, a strong correspondence between the volumes of the medulla oblongata and the cervical cord has been shown (Liptak et al, 2008). Thus, we interpret the present findings in the MS groups as predominantly disease related.…”
Section: Discussionmentioning
confidence: 60%
“…Although the brainstem is significantly atrophied when compared with matched control subjects, brainstem volume correlates weakly with the disability rating scales [44]. Nevertheless, measurements of medulla oblongata volume significantly correlate with upper cervical cord volume and, thus, can serve as a potential biomarker of spinal cord damage in MS [45].…”
Section: Mri In the Evaluation Of The Brainstem Involvement In Msmentioning
confidence: 97%